Implementation of Moodle LMS in Learning Islamic Education in Elementary Schools during the COVID-19 Pandemic - Nadia Risya Faridah; Syafi'i Syafi'i (Teknodika, 2021)
The ongoing COVID-19 pandemic has made education world always innovate in the learning process. Various applications and online learning strategies have become a new culture for educators and students. For this reason, this study aims to analyze the implementation, advantages, and disadvantages of the Moodle LMS in learning Islamic education at the elementary school level during the COVID-19 pandemic. This study used a qualitative-descriptive approach. Utilizing interview and observation data collection techniques, this study’s results revealed that the learning process of Islamic education was divided into three stages. The initial stage was the activity of opening by the teacher to students. Followed by the core stage, students carried out instructions by the teacher to access the Moodle according to the agreed time period. The last stage was the closing stage, where the teacher and students returned face to face to evaluate and pray together. Meanwhile, the advantages of Moodle LMS in learning covered a free and easy to use platform and supported several document types for the learning process. However, the disadvantages consisted of some foreign features for students, and the access times were slow if the owned bandwidth was not qualified.